2012
DOI: 10.1039/c1md00227a
|View full text |Cite
|
Sign up to set email alerts
|

Sangamides, a new class of cyclophilin-inhibiting host-targeted antivirals for treatment of HCV infection

Abstract: Sangamides are amide derivatives of sanglifehrin A, a cyclophilin-binding polyketide natural product which is structurally distinct from cyclosporine A. Cyclosporine A is the starting point for the synthesis of cyclophilin inhibitors such as alisporivir, currently in development for the treatment of HCV infection. We report here initial results of the optimisation program which led to identification of the sangamides, compounds that exhibit significantly improved potential for the treatment of chronic HCV infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 34 publications
1
29
0
2
Order By: Relevance
“…This prime discovery was corroborated by subsequent studies, which showed that not only CsA, but non-immunosuppressive CsA derivates such as NIM811, Alisporivir and SCY-635 also block HCV replication [7,13,14,15,16,17]. Moreover, studies showed that sanglifehrins as well as polyketide sanglifehrin derivates also inhibit HCV replication [14,18,19,20]. Sanglifehrins are natural products that also bind Cyps, but are structurally distinct from CsA [19].…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…This prime discovery was corroborated by subsequent studies, which showed that not only CsA, but non-immunosuppressive CsA derivates such as NIM811, Alisporivir and SCY-635 also block HCV replication [7,13,14,15,16,17]. Moreover, studies showed that sanglifehrins as well as polyketide sanglifehrin derivates also inhibit HCV replication [14,18,19,20]. Sanglifehrins are natural products that also bind Cyps, but are structurally distinct from CsA [19].…”
Section: Resultsmentioning
confidence: 91%
“…CypA possesses a hydrophobic pocket that contains both the enzymatic and ligand binding sites of the protein [29]. CsA, sanglifehrins and their derivates, by binding within this hydrophobic pocket, neutralize both the enzymatic and ligand binding activities of CypA [19,20]. Although CypA has been shown to act as a peptidyl-prolyl cis-trans isomerase in vitro , its true cellular function remains to be demonstrated.…”
Section: Resultsmentioning
confidence: 99%
“…5A). We also investigated DY m dissipation by siCK1 under pharmacological inhibition of CypD by treatment with cyclosporin A, sanglifehrin A, and compound BC544 (Moss, 2011). However, none of these CypD inhibitors had any effect on siCK1-induced mitochondrial membrane depolarization (Fig.…”
Section: Depletion Of Ckmt1 Results In Mptmentioning
confidence: 99%
“…CypI blocks HCV replication by neutralizing the enzymatic activity of CypA. We and others showed that CypA interacts directly with NS5A of multiple genotypes and that this interaction is abrogated by CypI (36)(37)(38)(39)(40)(41)(42)(43)(44)(45). Thus, there is a direct correlation between preventing NS5A-CypA interactions and blocking HCV replication.…”
mentioning
confidence: 80%